The types of withdrawal for EPF money at Malacca Branch / Zaiton Ishamudin - Ishamudin, Zaiton (2011)
The purpose of this study is to know the types of withdrawal at Employee Provident Fund (EPF). This study is focus on Malacca’s Employee Provident Fund at Ayer Keroh. It also wants to know what type of withdrawal that EPF member has always makes withdrawal their money from their account at EPF. Besides that, this study is also wants to know what the comparison between the monthly, quarterly and yearly that EPF member make withdrawal. So, this study is want to focus for the total of withdrawal like age 50 years withdrawal, age 55 years withdrawal, education withdrawal, purchase a house, reduce a balance for housing loan and for health withdrawal.